2019
DOI: 10.1186/s12871-019-0751-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of different degrees of passive leg raising on the internal jugular vein cross-sectional area in patients before thoracic surgery

Abstract: Background This study investigated the effect of different degrees of passive leg raising (PLR) on the internal jugular vein (IJV) cross-sectional area (CSA) and on the success rate of IJV cannulation in patients waiting for thoracic surgery, to analyze whether body mass index (BMI), gender, age, fasting time and preoperative rehydration have any impact on changes in the IJV CSA. Methods Eighty-two patients scheduled for selective thoracic surgery were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The success rate of central venous cannulation correlates with the venous cross-sectional area (CSA) 7–10. Techniques such as positive end-expiratory pressure, the Trendelenburg position, passive leg raising (PLR): a technique to elevate the patient’s legs to increase the venous return, and the Valsalva manoeuvre have been shown to increase the CSA of the IJV in anaesthetised patients 11–15. However, most studies evaluating the impact of these manoeuvres on IJV CSA have been conducted in patients with non-obesity 16 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success rate of central venous cannulation correlates with the venous cross-sectional area (CSA) 7–10. Techniques such as positive end-expiratory pressure, the Trendelenburg position, passive leg raising (PLR): a technique to elevate the patient’s legs to increase the venous return, and the Valsalva manoeuvre have been shown to increase the CSA of the IJV in anaesthetised patients 11–15. However, most studies evaluating the impact of these manoeuvres on IJV CSA have been conducted in patients with non-obesity 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Techniques such as positive end-expiratory pressure, the Trendelenburg position, passive leg raising (PLR): a technique to elevate the patient's legs to increase the venous return, and the Valsalva manoeuvre have been shown to increase the CSA of the IJV in anaesthetised patients. [11][12][13][14][15] However, most studies evaluating the impact of these manoeuvres on IJV CSA have been conducted in patients with non-obesity. 16 17 The effectiveness and safety of these techniques in patients with obesity remain debated, especially since studies like those by Ozkan et al have not found the Trendelenburg position to increase the CSA of the IJV in patients with obesity.…”
Section: Introductionmentioning
confidence: 99%